The Influence of Corporate Social Responsibility (CSR) on the Financial Performance of State-Owned Banks - Monintja, Frinsi Theresia; Rogahang, Joula J.; Mangindaan, Joanne Valesca (Productivity, 2025)
This study aims to determine the influence of Corporate Social Responsibility (CSR) on the financial performance of state-owned bank companies from 2016-2023. In measuring CSR, this study uses a ratio measurement scale based on CSR costs or expenses, which is calculated by the formula of total CSR expenditure divided by total net profit. A company’s financial performance is measured by the Return on Asset (ROA) ratio. Corporate Social Responsibility (CSR) is a corporate social responsibility that is realized through programs that aim to improve people’s welfare. ROA shows the company’s capacity to earn profits. The analysis used in this study is a simple linear regression analysis. The results of the study show that CSR has a significant negative effect on the financial performance of state-owned bank companies from 2016-2023.